Reasons for Dereliction in Implementation of Laws Related to Sexual Offences in India: Exploring the Challenges and Motivations in Implementing Sexual Offences Laws (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In present times, the cases of sexual assault and their lengthy trials have become the most complex matters which come before the Criminal Courts in India. Judiciary many times faces different problems while solving these matters. Taking other crimes into consideration like in case of murder, theft and non-sexual assault, the prosecution must establish that a crime has indeed been committed. Only then does it become necessary to enquire who committed it. People around the country threaten others to file a case against them in case any wrong happens with them. But things are completely different when it comes to offences related to sexual assault. As, in many cases, a girl is being raped and murdered but family members instead of asking for justice from the courts, declare it as an accident. They deny reporting the case. There may be various reasons for it say they are concerned about security of other woman in the house, it may ruin their respect or image in the society etc.